Static behavior of novel shear connectors with post-poured UHPC for prefabricated composite bridge. (September 2022) - Guo, Jincen; Zhou, Zhixiang; Zou, Yang; Zhang, Zhongya; Jiang, Jinlong; Wang, Xiaodong
Abstract: Stud connectors are commonly used in prefabricated composite bridges. However, the reserved holes required by the studs weaken the integrity of the bridge deck and lead to inefficient construction. To simplify the prefabrication procedures of the assembled composite bridge and realize rapid construction on-site, a precast concrete deck-steel beam-connection concrete (PCSC) connector with good integrity of bridge decks is proposed in this study. To achieve shear force transfer between the bridge deck and the steel beam, ultra-high performance concrete (UHPC) is employed as connecting concrete. The shear performance and failure mode of PCSC connectors were studied through static push-out tests and finite-element analysis, and the mechanical model of PCSC connectors was established. The failure mode of PCSC connectors was identified as stud failure in all experimental results. The ultimate capacity of studs in the UHPC specimen was 37% higher than that of high-strength mortar (HSM), while the interfacial slip between steel and connection concrete was 37% lower. Meanwhile, the shear stiffness of the stud in UHPC specimens was 22% and 42% higher than that of HSM specimens in elastic and plastic stages, respectively. To predict the load-slip behavior of PCSC connectors, an empirical load-slip formula for PCSC connectors was proposed, and current design codes for stud shear strength were evaluated. PCSC connectors are demonstrated to have improved bearing capacity and ductility when compared to conventional stud connectors.